2012
DOI: 10.1016/j.freeradbiomed.2011.10.444
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of benfotiamine are mediated through the regulation of the arachidonic acid pathway in macrophages

Abstract: Benfotiamine, a lipid-soluble analogue of vitamin B1, is a potent anti-oxidant that is used as a food supplement for the treatment of diabetic complications. Our recent study indicates a novel role of benfotiamine in the prevention of bacterial endotoxin, lipopolysaccharide (LPS)-induced cytotoxicity and inflammatory response in murine macrophages. Nevertheless, it remains unclear how benfotiamine mediates anti-inflammatory effects. In this study, we investigated the anti-inflammatory role of benfotiamine in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…Besides the central effects in lowering nociception, thiamine may reduce the inflammatory pain by lowering inflammation as it has been suggested that anti-inflammatory effect of this vitamin may be mediated through regulation of arachidonic acid pathway in macrophage, where it can block the expression of any of the enzymes (cycloxygenase-2, lipoxygenase-2, thromboxane B synthase, prostacycline synthase) as well as transcription factor nuclear factor kappa 54 . Moreover, this vitamin may also decrease the oxidative stress and production of free radicals 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the central effects in lowering nociception, thiamine may reduce the inflammatory pain by lowering inflammation as it has been suggested that anti-inflammatory effect of this vitamin may be mediated through regulation of arachidonic acid pathway in macrophage, where it can block the expression of any of the enzymes (cycloxygenase-2, lipoxygenase-2, thromboxane B synthase, prostacycline synthase) as well as transcription factor nuclear factor kappa 54 . Moreover, this vitamin may also decrease the oxidative stress and production of free radicals 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, thiamine supplementation may also increase the availability or effectiveness of serotonin as well as noradrenaline in the CNS 24,26,27 . Besides the central effects in lowering nociception, it has been proposed that peripheral anti-inflammatory effect of this vitamin may be mediated through regulation of arachidonic acid pathway in macrophage, where it can block the expression of any of the enzymes (cycloxygenase-2, lipoxygenase-2, thromboxane B synthase, prostacycline synthase) as well as transcription factor nuclear factor kappa 28 . In addition, this vitamin may also decrease the oxidative stress and production of free radicals 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, subcutaneous injection of formalin at hindpaw induces inflammation, which leads to a response characterized by jerking, flexing followed by licking of the affected hindlimb 23,25,26 . Pain intensity is measured by converting these behavioral responses into numerical values 24,25,26,27, assessed in early phase (first 5-7 minutes, results from direct chemical stimulation of the nociceptive afferent fibers mainly C fibers) 28 , while the late phase (last 40-45 minutes, results from the action of locally released inflammatory mediators and also by the facilitation of synaptic transmission in thespinalcord) 29 .…”
mentioning
confidence: 99%
“…Benfotiamine has also been reported to have anti-inflammatory effects. 76,77 Ang-2 is not expressed by pericytes; pericytes express Ang-1 (and not Ang-2), which promote EC survival signalling, maintenance of endothelial barrier and vascular maturation and quiescence [78][79][80][81] and reduces VEGF-stimulated leukocyte adhesion to ECs. 82 Taurine has been reported to inhibit high glucose-induced apoptosis in retinal pericytes through increased Tie-2 expression and downregulation of Ang-2.…”
Section: Angiopoietin (Ang)-2 Blockagementioning
confidence: 99%